2021
DOI: 10.1101/2021.10.25.465678
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic adaptation of the picoeukaryote Pelagomonas calceolata to iron-poor oceans revealed by a chromosome-scale genome sequence

Abstract: Eukaryotic phytoplankton are key actors in marine ecosystems, they contribute to atmospheric CO2 sequestration and supply organic matter to the trophic network. Among them, Pelagophytes (Stramenopiles) algae are a diverse class with coastal species causative of harmful algal blooms while others are cosmopolites and abundant in open ocean ecosystems. Despite their ecological importance, only a few genomic references exist limiting our capacity to identify them and study their adaptation mechanisms in a changing… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 100 publications
0
1
0
Order By: Relevance
“…Many studies based either on satellite ( 6, 7 ) or genomic data ( 4, 8, 9 ) revealed a mainly latitudinal and temperature driven biogeographical partitioning of the oceans. While some species have strictly defined environmental niches ( 4, 10 ), some display cosmopolitan biogeographies, such as Bathycoccus prasinos which is present in both polar and temperate oceans ( 11 ) or Pelagomonas calceolata that is cosmopolitan in all except polar oceans ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies based either on satellite ( 6, 7 ) or genomic data ( 4, 8, 9 ) revealed a mainly latitudinal and temperature driven biogeographical partitioning of the oceans. While some species have strictly defined environmental niches ( 4, 10 ), some display cosmopolitan biogeographies, such as Bathycoccus prasinos which is present in both polar and temperate oceans ( 11 ) or Pelagomonas calceolata that is cosmopolitan in all except polar oceans ( 12 ).…”
Section: Introductionmentioning
confidence: 99%